Forest Inventory Methodology and Applications - Kangas, Annika; Maltamo, Matti; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book has been developed as a forest inventory textbook for students and can also serve as a handbook for practical foresters. The book is divided into four sections. The first section deals mostly with sampling issues. First, we present the basic sampling designs at a fairly non-technical mathematical level. In addition, we present some more advanced sampling issues often needed in forest inventory. Those include for instance problems with systematic sampling, and methods for sampling vegetation or rare populations. Forest inventory also includes issues that are unique to forestry, like problems in measuring sample plots in the field, or utilising sample tree measurements. These issues include highly sophisticated methodology, but we try to present these also such that forestry students can grasp the ideas behind them. Each method is presented with examples. For foresters who need more details, references are given to more advanced scientific papers and books in the fields of statistics and biometrics. Forest inventories in many countries involve much more than sampling and measurement issues. Most applications nowadays involve remote sensing technology of some sort, so that section II deals with the use of remote sensing material for this purpose. Examples of multi-phase and multi-source inventory are presented. Methods suitable for special applications, like stand-level or global-level inventory, are also presented. Section III deals with national inventories carried out in different parts of the world. Examples of forest inventory in selected countries around the world are presented. Section IV is an attempt to outline some future possibilities of forest inventory methodologies.
Design-Based Sampling and Inference -- Model-Based Inference -- Mensurational Aspects -- Change Monitoring with Permanent Sample Plots -- Generalizing Sample Tree Information -- Use of Additional Information -- Sampling Rare Populations -- Inventories of Vegetation, Wild Berries and Mushrooms -- Assessment of Uncertainity in Spatially Systematic Sampling -- The Finnish National Forest Inventory -- The Finnish Multi-source National Forest Inventory - Small Area Estimationand Map Production -- Correcting Map Errors in Forest Inventory Estimates for Small Areas -- Multiphase Sampling -- Segmentation -- Inventory by Compartments -- Assessing the World's Forests -- Europe -- Asia -- North America -- Modern Data Acquisition for Forest Inventories.
Keywords: LIFE SCIENCES; REMOTE SENSING; FORESTS AND FORESTRY; STATISTICS; LIFE SCIENCES; FORESTRY; REMOTE SENSING/PHOTOGRAMMETRY.; STATISTICS FOR LIFE SCIENCES, MEDICINE, HEALTH SCIENCES